PERAN KECERDASAN BUATAN (AI) MULTIMODAL DALAM AKSELERASI PEMBELAJARAN KOSAKATA BAHASA ARAB - Azizah Pakaya; Neli Asmaniah; Siti Mustika Vevi Mokoginta; Abdul Hadi Al Muhdar; Ach. Faridhal Athros Al Farisi (STIT Darul Hijrah Martapura, 2026)
Vocabulary constitutes a fundamental component of Arabic language acquisition; however, many learners still encounter difficulties in understanding the meaning, pronunciation, and contextual use of vocabulary. Advances in Artificial Intelligence (AI) have led to the emergence of multimodal AI, which integrates text, audio, and visual elements into a more adaptive learning environment. This study aims to analyze the contribution of multimodal AI to accelerating Arabic vocabulary learning and to identify the challenges and opportunities associated with its implementation. The study employs a qualitative approach using a literature review design, with a systematic selection of relevant scholarly articles, conference proceedings, and research reports. Data were analyzed through content analysis and thematic analysis to identify patterns, consistencies, and research gaps. The findings indicate that multimodal AI accelerates vocabulary learning through the integration of text, audio, and visual modalities, which strengthens the connection between the form, pronunciation, and meaning of vocabulary items. In addition, multimodal AI enhances vocabulary retention, supports personalized learning, and provides authentic contextual exposure. Despite facing technological, linguistic, and pedagogical challenges, multimodal AI demonstrates significant potential to support more effective, adaptive, and contextualized Arabic vocabulary learning.